Effect of CPAP therapy on daytime function in patients with mild sleep apnoea/hypopnoea syndrome - Engleman, H. M. (BMJ Group, 1997)
BACKGROUND: Continuous positive airway pressure (CPAP) is an effective treatment in patients with moderate and severe sleep apnoea/hypopnoea syndrome (SAHS), but the minimum illness severity at which patients obtain benefit from CPAP is unclear. A study was therefore undertaken to investigate whether CPAP improves symptoms and daytime function in patients with mild SAHS. METHODS: Sixteen consecutively recruited patients with mild SAHS (5.0-14.9 apnoeas + hypopnoeas per hour slept and two or more symptoms of SAHS) participated in a prospective placebo controlled randomised crossover trial to assess the effects of CPAP on symptoms and daytime function. Patients spent four weeks on placebo and four weeks on CPAP, undergoing assessments of sleepiness, symptoms, cognitive performance, and well being on the last day of each treatment. Data from the placebo and CPAP assessments were compared. RESULTS: The mean (SE) objective effective use of CPAP was 2.8 (0.7) hours per night. Significant improvements in symptom score (-1.7 (0.5), p < 0.01), mental flexibility (-14 (5) seconds, p = 0.02), and depression rating (-1.6 (0.8), p = 0.03) on CPAP were observed. However, no significant differences in subjective or objective sleepiness were found. Ten of the 16 patients preferred CPAP and opted to continue with this treatment, although this proportion was non- significant (p > 0.4). The eight patients with best CPAP use showed an additional CPAP related improvement in quality of life (-4.4 (1.8), p = 0.03). Those who complied better with CPAP therapy also had a higher average microarousal frequency (p < 0.01) and apnoea+hypopnoea index (p = 0.02) than the poorer compliers. CONCLUSIONS: The results of this study provide evidence for improvements in symptoms and daytime function for patients with mild SAHS treated with CPAP.